Effect of Heat Stress, Dietary Electrolytes, and Vitamins E and C on Growth Performance and Blood Biochemistry of the Broiler Chicken - Livingston, Matthew L.; Pokoo-Aikins, Anthony; Frost, Thomas; Laprade, Lisa; Hoang, Vy; Nogal, Bartek; Phillips, Chelsea; Cowieson, Aaron J. (Frontiers in Animal Science, 2022)
Environmental heat stress creates a detriment to the welfare and performance in broiler chickens. While there are some dietary mineral and vitamin supplements that mitigate this condition, a rapid, plasma-based detection method would improve management response and broaden the scientific understanding of heat stress. A total of 960 broilers were used to determine the effect of heat stress and dietary electrolyte balance on blood biochemistry. Sex sorted chicks were allocated to 48 pens with 20 chicks per pen creating 6 treatments (3 diets x 2 house environments) with eight replicates and fed one of three dietary treatments: a control containing primarily sodium chloride (NaCl), a heat stress formulation containing bicarbonate (NaHCO3), or heat stress fortified with 200 ppm vitamin C and E (NaHCO3 Fortified). Birds were housed in two different temperature-controlled environments either a thermoneutral (Control) or heat stressed (Heat Stress) environment. At day 28, 35 and 42 venous blood was collected and analyzed using rapid detection methods followed by post-mortem veterinary evaluations. Performance was measured at weekly intervals. Mortality was significantly higher in broilers exposed to heat stress as compared to thermoneutral, while broilers that received dietary sodium chloride also had higher mortality than bicarbonate fed birds. Heat stress significantly impacted potassium, hematocrit, uric acid, total protein, globulin, hematocrit, lymphocytes, sodium, and glucose. This study demonstrates that blood biochemistry of broiler chickens is influenced by dietary intervention and changing environmental conditions. This pattern suggests a blood biomarker footprint of sub-optimal nutrition or poor environmental conditions that may provide valuable information into physiological changes in response to dietary electrolytes, vitamins, and heat stress. Furthermore, this footprint may potentiate the development of diagnostic tools, combining biomarkers to determine nutrition and health status of individual broiler flocks, for nutritionists, veterinarians, and live production managers to manage flocks for environmental, humane, and productive purposes.